1982
DOI: 10.1111/j.1365-2648.1982.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring nurses' accuracy of estimating blood loss

Abstract: Estimation is the most commonly used method to determine blood loss. According to the literature, estimating blood loss is not exact; there are wide margins of error and blood loss tends to be underestimated. Forty-two registered nurses were asked to estimate varied amounts of blood on 20 peripads. Both over- and underestimation occurred; 71% overestimated and 25% underestimated blood loss. There was also disagreement as to what constituted heavy, moderate or slight blood loss. There was no difference in accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…results also are found in comparable studies and reports, including estimations by doctors, nurses, and midwives. [5][6][7][8][9][10] No other studies have investigated whether preemployment (pre-registration), undergraduate, paramedic, university students can accurately estimate external blood loss or whether university students' lack of experience and exposure makes them less accurate. No formal integration of previous research in this area has been included in undergraduate paramedic learning objectives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…results also are found in comparable studies and reports, including estimations by doctors, nurses, and midwives. [5][6][7][8][9][10] No other studies have investigated whether preemployment (pre-registration), undergraduate, paramedic, university students can accurately estimate external blood loss or whether university students' lack of experience and exposure makes them less accurate. No formal integration of previous research in this area has been included in undergraduate paramedic learning objectives.…”
Section: Resultsmentioning
confidence: 99%
“…These findings have educational implications for undergraduate paramedic curriculum, education, and training requirements.The inaccurate estimations in this study also are supported by other prehospital studies, 1,3,4 and additionally in other allied health professions. [5][6][7][8][9][10] Generally, students were accurate with their estimations on the vinyl surface. Moscati et al found similar findings in the study, where students estimated differing amounts on porous and non-porous surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anesthesiologist in this study was also an experienced physician, but it has been demonstrated that the accuracy of PBL estimation is unrelated to seniority or experience. 16 , 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Six observational studies (4)(5)(6)(7)(8)(9), with a total of 594 participants, compared visual estimation with known values in the delivery room or in simulated scenarios. Three studies (10-12) compared visual or quantified estimations with laboratory measurement in 331 vaginal deliveries.…”
Section: Visual Versus Quantitative Methods For Estimating Blood Lossmentioning
confidence: 99%